PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN DAUR ULANG DAN PENGELOLAAN SAMPAH KARTON DI DESA JARAK PLOSOKLATEN - Yap, Nonni; Laely, Nur; Wardani, Denvi Nur Mei; Nugroho, Rian Dimas (Jurnal Abdi Masyarakat, 2021)
There are many types of creative business ideas, but an interesting creative business idea is if someone can turn a waste into a handicraft that can generate profits and moreover can be sold. Cardboard waste is one of the wastes that can be reprocessed into a useful handicraft. By empowering existing human resources in Jarak Village, Ploso Klaten District, Kediri Regency, this Community Servicse activity is carried out by providing entrepreneurial insight, providing training to make handicrafts from cardboard waste. As a result of this activity, the community in the Jarak Village, Ploso Klaten District, Kediri Regency, got additional entrepreneurial insights which included how to obtain raw materials, production techniques and product marketing.